JURIDICAL ANALYSIS OF PROVING GUILT IN PARTICIPATING IN THE CRIME OF THEFT ACCORDING TO PROVISIONS OF ARTICLE 55 OF THE CRIMINAL CODE (Study Decision Number: 15/Pid.S/2024/PN.Stb) - Asmita Br. Sitepu; Mhd. Azhali Siregar (International Journal of Society and Law, 2025)
This study examines and examines participation (deelneming) which, among other things, includes the form of participation/involvement of a person both psychologically and physically by doing an act so that a criminal act occurs. The inclusion penalty is regulated in Article 55 of the Criminal Code which means that there are two or more people who commit a criminal act. This research is a type of normative research using secondary legal sources and using qualitative descriptive analysis. The results of this study show that the forms of participation can be divided into two parts, namely: first, the maker consisting of: the actor (pleger), the doenpleger, the participant (madepleger) and the advocate (uitlokker); Second, the helper consists of: the helper at the time the crime is committed and the helper before the crime is committed.